Marxism in the modern world: social-philosophical analysis - KHAZOEVA, N.O.; KHAZIEV, A.K.; KLYUSHINA, E.V.; STEPANENKO, G.N.; STEPANENKO, R.F. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The paper concentrates on resolving the question: is it possible today to be guided by Marxism as an instrument of social transformation, is this teaching capable of contributing to social advancement? Facts are a stubborn thing: Marxism in its completeness is refuted. But the fact of the collapse of the attempts to put Marxism into practice is not a completely convincing argument against the social doctrine of Marx. The question, ultimately, goes back to the problem of the subjective factor of the moral, theoretical, and political maturity of those who turn Marxism in actual practice. RESUMEN El documento se concentra en resolver la pregunta: ¿es posible hoy ser guiado por el marxismo como instrumento de transformación social? ¿es esta enseñanza capaz de contribuir al avance social? Los hechos son obstinados: el marxismo en su integridad es refutado. Pero el hecho del colapso de los intentos de poner en práctica el marxismo no es un argumento completamente convincente contra la doctrina social de Marx. La cuestión, en última instancia, se remonta al problema del factor subjetivo de la madurez moral, teórica y política, de quienes transforman el marxismo en la práctica real.